2011
DOI: 10.1258/ijsa.2011.010481
|View full text |Cite
|
Sign up to set email alerts
|

Asking about condom use: a key to individualized care when screening for chlamydia

Abstract: Chlamydia trachomatis (CT) infection has been a target for both selective and national screening programmes, and Sweden has an opportunistic approach. A national plan of action states that risk groups should be identified and offered risk reduction counselling. Patients attending a drop-in sexually transmitted infection (STI) clinic reception at the University Hospital, Umeå, Sweden, were invited to complete a questionnaire regarding sociodemographic characteristics, symptoms and sexual risk behaviour; all had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…The finding of clustering of sexual risk-taking behaviours, violence exposure and outcomes such as rates of STIs and unintended pregnancy is in agreement with the results of both national and international studies [2][3][4]32], some of which have proposed that extended screening be performed by sexual health services [2,4,27]. To our knowledge, the clinical screening endeavours described in the scientific literature only focus on specific forms of ill health, which limits possible comparisons: child sex trafficking [9], violence victimisation [47,51], chlamydia [52] and alcohol use [53]. The questions and procedures in the mentioned studies are, however, similar to those of the present study, further supporting the feasibility of this approach to better identify youth with sexual health needs, when they come into contact with health care professionals.…”
Section: Similarities and Differences In Relation To Other Studiessupporting
confidence: 84%
“…The finding of clustering of sexual risk-taking behaviours, violence exposure and outcomes such as rates of STIs and unintended pregnancy is in agreement with the results of both national and international studies [2][3][4]32], some of which have proposed that extended screening be performed by sexual health services [2,4,27]. To our knowledge, the clinical screening endeavours described in the scientific literature only focus on specific forms of ill health, which limits possible comparisons: child sex trafficking [9], violence victimisation [47,51], chlamydia [52] and alcohol use [53]. The questions and procedures in the mentioned studies are, however, similar to those of the present study, further supporting the feasibility of this approach to better identify youth with sexual health needs, when they come into contact with health care professionals.…”
Section: Similarities and Differences In Relation To Other Studiessupporting
confidence: 84%
“…7 9 10 12 22 Younger individuals (20–24 years) had a significant two times higher risk to be diagnosed with chlamydia compared with those 35–40 years, and this was consistent with earlier reports on higher chlamydia risk among younger individuals, which might be attributed to the higher number of sexual partners and lower condom use in the younger individuals, which was supported by descriptive results in our study 67 9 10 Furthermore, study participants who reported contact with a chlamydia case (having a partner with chlamydia or receiving a contact tracing letter) were strongly associated with increased risk of chlamydia.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, studies about risk factors for chlamydia infection have been scattered in time and population. These include studies on healthcare clinic patients,12–14 in the general population with a focus on socioeconomic factors with self-reported chlamydia status,15 and in self-recruited users of a website for ordering home-based chlamydia sampling kits 16. Owing to the change in the sexual behaviour of the general population over the past two decades17 and lack of recent evidence on factors associated with chlamydia, this study was initiated in Sweden in a population with expected higher prevalence of chlamydia and other STIs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our risk assessment model, young age and increasing number of sexual partners predicted chlamydia, and the main difference was that in the Dutch study, socio-demographic factors also had an impact. In clinic-based studies, symptoms of chlamydia have also been demonstrated as a predictor [21,22]. Results from different studies may partly vary depending on the variables used and by the setting and country of the study.…”
Section: Discussionmentioning
confidence: 99%